Casabe: A bread that has been around for 3000 years or more - Pérez Mujica, Bárbara; Cadenas Uscategui, Sergia; Aguiar, José Gregorio; Valero López, Sandra (SATHIRI, 2025)
Casabe is a very old food. Historically, it was the Arawaks, aborigines from northern South America, who began to make it by hand. Its origin dates back to the 18th century, since this time people have talked about this delicacy in Venezuela and it is found within Venezuelan gastronomy because it is a traditional component that cannot be missing in most homes in our country. This thin, lightweight cake, derived from cassava, has been claimed for more than 3.000 years. Cassava has a variety of foods that are located in a privileged place, occupying a prominent space in the dietary consumption of Venezuelans since the 16th century. However, in Caracas it also has its place of honor. Hence, the objective of this study is: to make theoretical contributions about casabe, starting from its historical aspects, until reaching the facts that have contributed to its permanence over time and its growing consumption. The methodology is a bibliographic design, with features of transversality and descriptivism, while the type of research is documentary and its level is historical, since the past is analyzed, to give way to other aspects inherent to future constructs.